The IL-33-PIN1-IRAK-M axis is critical for type 2 immunity in IL-33-induced allergic airway inflammation - Morris Nechama (Nature Portfolio, 2018)
IL-33 orchestrates type 2 immunity in allergic asthma. Here the authors show, using biochemical, structural and patient data, that upon IL-33 or allergic challenge, the isomerase Pin1 modifies IRAK-M to control the production of pro-inflammatory cytokines in the setting of airway inflammation.